Student nurses' experiences during clinical practice in the Limpopo Province - BT Mabuda (AOSIS, 2008)
A qualitative, exploratory, descriptive and contextual study was conducted to explore student nurses' experiences during clinical practice at a nursing college in the Limpopo Province. Purposive sampling was used and phenomenological interviews were held with eleven (11) student nurses who were in their final year of the four year basic nursing programme. The interviews were analysed by using Tesch's method of data analysis for qualitative research. The findings indicate that there are aspects which impact negatively on student nurses' clinical learning experiences, such as lack of teaching and learning support, lack of opportunities for learning, poor theory-practice integration, and poor interpersonal relationships between the students, college tutors and ward staff. Recommendations to enhance the clinical learning experiences of student nurses were outlined.